2012
DOI: 10.1007/s00066-011-0029-4
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitizing effect of epothilone B on human epithelial cancer cells

Abstract: The results of this study showed that epothilone B displays cytotoxic antitumor activity at low nanomolar concentrations and also enhances the radiation response in the tumor cells tested; this may be induced by a reduced DNA repair capacity triggered by epothilone B. It was also demonstrated that epothilone B in fact targets microtubules in a more effective manner than paclitaxel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…The interaction modality between photons or protons and Epothilone B in A549 and U251MG cells is slightly synergistic. Our results with photon beam on A549 cells are in agreement with those of Baumgart (Baumgart et al 2012), who found for the same cell line a synergistic effect of Epothilone B used in combination with photon beams irradiation. As far as we know there are no published studies on the use of Epothilone B in combination with proton beam irradiation on A549 or U251MG cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The interaction modality between photons or protons and Epothilone B in A549 and U251MG cells is slightly synergistic. Our results with photon beam on A549 cells are in agreement with those of Baumgart (Baumgart et al 2012), who found for the same cell line a synergistic effect of Epothilone B used in combination with photon beams irradiation. As far as we know there are no published studies on the use of Epothilone B in combination with proton beam irradiation on A549 or U251MG cells.…”
Section: Discussionsupporting
confidence: 93%
“…To measure cell clonogenic survival, cells were detached from the flask immediately after irradiation using 0.25% Trypsin-EDTA, counted, reseeded in 5 T25 flasks for each dose/ treatment at suitable concentration and incubated for about 13 days. Incubation time intervals for clonogenic survival of these human cell lines reported in the literature are between 10 and 14 days (Baumgart et al 2012, Rohrer Bley et al 2009. The cells were then fixed with ethanol and stained with 10% Giemsa solution and colonies consisting of more than 50 cells were scored as survivors.…”
Section: Clonogenic Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Though some links between those two machineries have been reported (Baschal et al, 2006; Lee et al, 2010; Lee et al, 2011; Xie et al, 2011), the conserved link described here points to a more general connection, whose exact physiological role and mechanistic details - in particular the cytoskeletal DDR target(s) involved - will need to be clarified. This might be of particular therapeutic relevance as a combination of cytostatic doses of DNA-damaging drugs with microtubule drugs has been shown to result in selective cytotoxicity and radio-/chemo-sensitisation in some cancer cells (Baumgart et al, 2012; Blagosklonny et al, 2000; Lee et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…(56,57) Furthermore there seems to be a tendency toward a concentration-dependent increase in DNA double strand breaks after combined treatment, suggesting a reduction of DSB repair capacity as an additional mechanism of sensitization. (46) Reoxygenation theory (biological cooperation, temporal modulation). The enhanced radiation response of combined treatment with microtubule stabilizing agents and ionizing radiation has also been attributed to "tumor cell reoxygenation".…”
Section: Rationale For the Combined Use Of Irradiation And Cytotoxic mentioning
confidence: 99%